Peran Guru BK dalam Membentuk Kepribadian Siswa - Nur Hasanah Harahap; Restu Amanda; Zahara Al Munawaroh; Ozza Rizwana Akila (Departement of Mathematics Education, 2023)
Guidance and Counseling teachers play an important role in determining the personality of their students. The importance of a good personality and the ideals of a teacher who guides students is an aid to conflicts faced by students, including shaping the personality of their students. The main responsibility of a BK teacher is to become a professional educator to teach, guide, lead, educate, assess and evaluate PAUD students through formal education, basic education, and secondary education.